2006
DOI: 10.2337/diabetes.55.01.06.db05-1129
|View full text |Cite
|
Sign up to set email alerts
|

Novel Leptin Receptor Mutation in NOD/LtJ Mice Suppresses Type 1 Diabetes Progression

Abstract: Recently, we identified in normally type 1 diabetes-prone NOD/LtJ mice a spontaneous new leptin receptor (LEPR) mutation (designated Lepr db-5J ) producing juvenile obesity, hyperglycemia, hyperinsulinemia, and hyperleptinemia. This early type 2 diabetes syndrome suppressed intraislet insulitis and permitted spontaneous diabetes remission. No significant differences in plasma corticosterone, splenic CD4؉ or CD8 ؉ T-cell percentages, or functions of CD3؉ T-cells in vitro distinguished NOD wild-type from mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…This last point is supported by data from other studies [6][7][8] that show a clear relationship between insulin resistance measured during IVGTT tests and the development of clinical diabetes if beta cell function is considered in the statistical model. The notion that obesity and insulin demand do not affect the presentation of autoimmunity is also supported by animal models in which severely obese mice that were genetically susceptible to type 1 diabetes rarely developed the disease [25,26]. Indeed, it appears that the obesity protected from the development of autoimmunity in these mice, although it is possible that the leptin receptor mutation introduced into the mice may have conferred protection independently from the obesity.…”
Section: Discussionmentioning
confidence: 98%
“…This last point is supported by data from other studies [6][7][8] that show a clear relationship between insulin resistance measured during IVGTT tests and the development of clinical diabetes if beta cell function is considered in the statistical model. The notion that obesity and insulin demand do not affect the presentation of autoimmunity is also supported by animal models in which severely obese mice that were genetically susceptible to type 1 diabetes rarely developed the disease [25,26]. Indeed, it appears that the obesity protected from the development of autoimmunity in these mice, although it is possible that the leptin receptor mutation introduced into the mice may have conferred protection independently from the obesity.…”
Section: Discussionmentioning
confidence: 98%
“…Leptin accelerates the disease onset and progression by stimulating autoimmune destruction of b-cells and significantly increased IFN-c production in peripheral T-cells (Matarese et al, 2002b). A recent study has shown that a spontaneous mutation of the leptin receptor in normally type 1 diabetes-prone NOD mice suppresses T1D development in the NOD mice by inhibiting activation of T-effector cells, demonstrating the important role of leptin signaling in the disease pathogenesis (Lee et al, 2006). Finally, leptin appears to also play a role in chronic graft-versus-host disease (cGVHD) in patients who receive hematopoietic stem cell transplantation (Tauchmanova et al, 2004), in which increased serum leptin levels are associated with the development of cGVHD.…”
Section: Leptin and Autoimmunitymentioning
confidence: 97%
“…9 More recent studies clearly showed that lack or inhibition of leptin/leptin receptor pathway protects against the development of various immunoinflammatory diseases in experimental models, ranging from colitis 31 to encephalomyelitis 11,12 or diabetes. 32 Protection was associated, at least in some experiments, 12 with a shift of the cytokine profile toward increased Th2/Treg type, increased expression of Foxp3, and increased number of Treg cells in lymphoid organs of mice with defective leptin signaling. These studies were also consistent with clinical findings showing a switch from Th1 toward Th2/Treg cytokine profile in individuals with leptin or leptin receptor deficiency, 33,34 and an inverse relationship between leptin secretion and the number of Treg cells in patients with multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%